Strategic Complementarities in a Model of Commercial Media Bias - Anna Kerkhof; Johannes Münster (Center for Economic Studies and ifo Institute (CESifo), 2023)
Media content is an important privately supplied public good. While it has been shown that contributions to a public good crowd out other contributions in many cases, the issue has not been thoroughly studied for media markets yet. We show that in a standard model of commercial media bias, qualities of media content are strategic complements, whereby investments into quality crowd in further investments and engage competitors in a race to the top. Therefore, financially strong public service media can mitigate commercial media bias: the content of commercial media can be more in line with the preferences of the audience and less advertiser-friendly in a dual (mixed public and commercial) media system than in a purely commercial media market.
Keywords: C70; H41; L13; L51; L82; 330; commercial media bias; public service media; advertising two-sided markets; supermodular games; strategic complements; public goods